Peranan Pendamping dalam Pengolahan Pupuk Organik dengan Teknologi Osaki Jepang (Kasus Sipadu 096 Desa Saba Kecamatan Blahbatuh Kabupaten Gianyar) - NUGRAHA, I MADE INDRAYANA; PUTRA, I GEDE SETIAWAN ADI; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p22, 2022)
The Role of Companion in Organic Fertilizer Management with Technology of Osaki Japan   (Case of Sipadu 096, Saba Village, Blahbatuh District,  Gianyar Regency) Sipadu 096 is one of sipadu in Gianyar where they produce fertilizer using Osaki Japan technology, so it produces a good quality fertilizer. The average of fertilizer production reached 2-3 tons each month in 2019. The purpose of this study is to find out the role of companion in organic fertilizer management with technology of Osaki Japan as a communicator, supervisor, facilitator, organizer, and motivator. The selection of the study location used deliberately method with method of qualitative descriptive analysis. The results of the study of the companion’s role as a communicator, supervisor, facilitator, organizer, and motivator was categorized good. The role of companion as a communicator in organic fertilizer management of Osaki Japan was categorized very good. The role of companion as a supervisor in organic fertilizer management of Osaki Japan got a good category. The role of companion as a facilitator got a very good category. The companion’s role as an organizer also got a very good category, and the role of companion as a motivator in organic fertilizer management of Osaki Japan got a good category.